Correlation between Head Computed Tomography Scan, Pre-operative Blood Lactate, and Pre-operative Glucose Level in Acute Traumatic Subdural Hematoma - Jefri Henky; Ahmad Faried (Majalah Kedokteran Bandung, 2021)
Acute traumatic subdural hematoma (SDH) is a focal brain injury resulting in alteration of cerebral perfusion and glucose metabolism, which would also results in hyperglicemia-induced-hyperlactatemia. A cross-sectional study was performed to analyze acute traumatic SDH patients by head CT scan and observe the effect on pre-operative blood lactate and blood glucose levels in 40 acute traumatic SDH patients at Dr. Hasan Sadikin Hospital, Bandung, Indonesia during the period of July-September 2013. Somers' D correlation were used in the analysis with a p-value of ≤0.05 considered as significant with 95% confidence interval. The mean values of pre-operative blood lactate and blood glucose levels were 3.16±1.49 mmol/L and 155.85±32.95 mg/dl, respectively with a strong positive correlation between the hematoma thickness and the increase in blood lactate (r= 0.656; p= 0.021) and a moderate positive correlation with increased blood glucose (r= 0.556; p= 0.025). In addition, the compressed cistern also had a very weak positive correlation with increase in blood lactate (r =0.156; p=0.043) and very weak positive correlation with increase in blood glucose (r= 0.139; p=0.056) while the midline shift had a weak positive correlation with increased blood lactate (r=0.353; p= 0.041) and a weak positive correlation with increased blood glucose (r = 0.333; p= 0.046). In conclusion, increased hematoma thickness, compressed cistern, and midline shift seen on head CT scan correlate with increasing blood lactate and glucose levels in acute traumatic SDH. Head CT scan, blood lactate level, and blood glucose level can be considered as one of the routine examinations to determine acute traumatic SDH severity at the macroscopic and cellular level.